Pemberdayaan Politik Perempuan Desa dan Peran Organisasi Masyarakat Sipil - Siti Azizah Namirah; Ida Ruwaida (Yayasan Jurnal Perempuan, 2023)
This article reviews the role of civil society organizations (CSOs) in collective empowerment, in order to encourage women to transform their gender roles, especially in the political field. Various studies on women’s political empowerment have been carried out, but most of them still focus on the issue of participation and not much has discussed women’s collective action. Therefore, political empowerment in this study is seen in a more comprehensive manner by referring to the conception of Sundström et al. (2017), namely from the dimensions of choice, agency, and participation. This article is more based on a literature review which is supported by the results of a case study at Yayasan PEKKA, known as a CSO which focuses its activism on women, especially in rural areas. The findings of the study show that the empowerment process in principle begins with strengthening individual capacity, but women’s critical power and ability to articulate the interests of women and other marginal groups is still questionable (choice dimension). This is a modality for strengthening group and institutional capacity (agency dimension), so as to be able to encourage the active role of women in various stakeholder forums both at the village and district levels (participation dimension). An integrative and sustainable model of empowerment is needed to strengthen women’s political position, including encouraging women’s power-within-based leadership, namely leadership that promotes collective action, or what is known as social power.